Depictive Criticism of The Application of Islamic Values in The Sulaimaniyah Islamic Boarding School Building - Muhammad Al Muttawaqil (Winaya Inspirasi Nusantara Foundation, 2022)
Islamic values have a very important role for a boarding school or boarding school in Aceh or Indonesia. The existence of Islamic boarding schools in Aceh has become a place to study good and true religion and is ignorant of people who have little knowledge in Islamic religious knowledge. This writing discusses Islamic values at a pesantren in Aceh. The research method used is a field study method by direct service to the location of the Sulaimaniyah Islamic Boarding School to obtain information about the buildings, facilities and facilities available at the Sulaimaniyah Islamic Boarding School. So, the conclusion is that all Islamic boarding schools in Aceh use or apply modern architecture and Islamic values such as the Sulaimaniyah Islamic Boarding School.